A method for producing a quartz glass tube for a semiconductor with low impurities
Patent Information
- Application Number
- CN202610862591.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-09
AI Technical Summary
[0011]本发明的目的在于提供一种低杂质半导体用石英玻璃管的制备方法,以解决现有技术中的半导体用石英玻璃管制备方法无法同时实现超低金属杂质、超低羟基含量、无气泡缺陷和较高生产效率,难以满足3nm及以下先进半导体制造工艺严苛要求的技术问题
1、通过超导磁选-分步梯度酸洗-高温晶型转变煅烧-定向水淬-微泡超声二次酸洗的组合工艺,不仅能够去除石英砂表面的杂质,还能通过高温晶型转变和定向水淬产生均匀的径向微裂纹,使酸液深入颗粒内部,有效去除微米级包裹体形式存在的金属杂质,特别是铝、钛、硼等难去除杂质,将原料中的总金属杂质含量降至0.08ppm以下。
Smart Images

Figure CN122878002A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of quartz glass manufacturing technology, and more specifically, to a method for preparing a low-impurity semiconductor quartz glass tube. Background Technology
[0002] Quartz glass, due to its excellent thermal stability, chemical stability, optical properties, and electrical insulation properties, has become an indispensable key material in semiconductor manufacturing processes, and is widely used in core components such as diffusion furnace tubes, oxidation furnace tubes, quartz boats, quartz crucibles, and etching cavities. As semiconductor technology advances towards 3nm and below nodes, the purity requirements for quartz glass materials have reached unprecedented levels, with total metal impurities required to be below 0.1ppm, hydroxyl content below 1ppm, and bubble density below 0.01 bubbles / cm³.
[0003] In existing technologies, the main methods for preparing quartz glass tubes for semiconductors include electrofusion, gas refining, and chemical vapor deposition (CVD). Electrofusion method: High-purity quartz sand is used as raw material, and the mixture is melted by electric heating in a tungsten-molybdenum crucible or graphite crucible and then drawn into shape. This method has high production efficiency and low cost, but it suffers from serious crucible contact contamination problems, resulting in high levels of impurities such as tungsten, molybdenum, and carbon in the product. The total metal impurity content is usually in the range of 1-5 ppm, which cannot meet the requirements of advanced semiconductor processes.
[0004] Gas refining method: Quartz sand is melted using an oxyhydrogen flame and deposited onto a rotating target to form a glass ingot, which is then processed into tubing. This method produces high purity, but the water vapor generated by the oxyhydrogen flame combustion results in a hydroxyl content as high as 150-200 ppm in the product, which seriously affects the material's thermal stability and infrared transmittance. Furthermore, the subsequent dehydroxylation process is complex and difficult to reduce the hydroxyl content to below 1 ppm.
[0005] CVD method: Using gaseous precursors such as silicon tetrachloride as raw materials, silicon dioxide is generated through high-temperature hydrolysis or oxidation reaction and then deposited into shape. This method can obtain products with extremely high purity, but the production efficiency is extremely low, the cost is high, and it is difficult to produce large-diameter (diameter > 200 mm) pipes, which cannot meet the needs of large-scale production.
[0006] In addition, existing technologies have the following shortcomings in impurity control: It is usually difficult to completely remove metallic impurities in the form of micron-sized inclusions in quartz sand by simply using acid washing or simple calcination and water quenching processes, especially difficult-to-remove impurities such as aluminum, titanium, and boron.
[0007] The lack of effective online purification methods during the melting process makes it impossible to remove impurities that have entered the melt, and the process can only rely on the purity of the raw materials, making it difficult to further improve the purity of the product.
[0008] The dehydroxylation process is usually carried out separately after molding, which not only increases the process flow and energy consumption, but also easily introduces new contamination during transfer and heating.
[0009] Low temperature control precision and unreasonable temperature gradient settings during tube drawing can easily lead to defects such as bubbles, air lines, and internal stress, affecting the optical uniformity and mechanical strength of the product.
[0010] In view of this, the present invention is proposed to solve the above-mentioned technical problems. Summary of the Invention
[0011] The purpose of this invention is to provide a method for preparing low-impurity semiconductor quartz glass tubes, in order to solve the technical problem that existing semiconductor quartz glass tube preparation methods cannot simultaneously achieve ultra-low metal impurities, ultra-low hydroxyl content, no bubble defects, and high production efficiency, making it difficult to meet the stringent requirements of advanced semiconductor manufacturing processes at 3nm and below.
[0012] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a low-impurity semiconductor quartz glass tube includes the following steps: S1. High-purity quartz sand with SiO2 content ≥ 99.9995% is subjected to superconducting magnetic separation, stepwise gradient acid washing, high-temperature crystal transformation calcination, directional water quenching and microbubble ultrasonic secondary acid washing treatment in sequence to obtain pretreated quartz sand. S2. Add the pretreated quartz sand to the vacuum induction suspension melting furnace and evacuate to a vacuum degree ≤ 5 × 10⁻⁶. -4 Pa, start the heating system to raise the temperature to 1500℃ at a rate of 50-100℃, hold for 10 minutes to remove adsorbed gas, and carry out suspension melting at a temperature of 2120-2180℃ to completely melt the quartz sand to form quartz glass melt. S3. In the process of suspension melting, online gas phase co-purification is carried out. A mixture of high-purity chlorine and high-purity argon with a flow ratio of 1:6-1:9 is simultaneously introduced into the melting furnace. The mixture is evenly introduced into the melt 5-10mm above the melt through an annular porous distributor. The pressure inside the furnace is maintained at 60-90Pa and the mixture is continuously introduced for 35-55 minutes. S4. The purified quartz glass melt is introduced into the tube drawing device, and continuous tube drawing is carried out using a three-stage gradient temperature field. The tube drawing speed is 0.8-1.8 m / min. During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.15-0.25 MPa. S5. While drawing the tube, the freshly drawn quartz glass tube is subjected to in-situ infrared heating to remove hydroxyl groups. The heating temperature is 1120-1180℃ and the holding time is 7-13 minutes. Then, it is slowly cooled to room temperature at a rate of 50-100℃ / min under the protection of high-purity argon. S6. After cooling, the quartz glass tube is cut, the end face is ground and cleaned in a Class 100 cleanroom, then vacuum dried at 105-115℃ for 2.5-3.5 hours, and finally purged with high-purity nitrogen and packaged to obtain the final product.
[0013] Furthermore, the superconducting magnetic separation is performed by using a superconducting high gradient magnetic separator with an field strength of 2-3T for two magnetic separations. The first magnetic separation removes strongly magnetic impurities, and the second magnetic separation removes weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand is ≤0.002%.
[0014] Furthermore, the stepwise gradient pickling is as follows: First acid washing: Soak the magnetically separated quartz sand in a hydrofluoric acid solution with a mass fraction of 11-14% at 65-75℃ for 28-44 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Soak in a 22-28% nitric acid solution at 85-95℃ for 14-22 hours, stirring every 6 hours for 20 minutes each time; Third pickling: Soak in a 6-9% hydrochloric acid solution at 65-75℃ for 7-11 hours, stirring every 4 hours for 15 minutes each time.
[0015] Furthermore, the high-temperature crystal transformation calcination is performed by heating the acid-washed quartz sand to 1230-1270℃ in air at a rate of 5-10℃ / min, holding it at that temperature for 5-7 hours to completely transform the quartz sand into the β-cristobalite crystal form, and then cooling it to room temperature in the furnace.
[0016] Furthermore, directional water quenching involves: holding the calcined quartz sand at 1200℃ for 30 minutes, and then rapidly immersing it in ultrapure water at a temperature of 6-9℃ by free fall. During the water quenching process, the ultrapure water is kept circulating at a flow rate of 0.5-1m / s, causing uniform radial microcracks to form in the quartz sand particles.
[0017] Furthermore, the microbubble ultrasonic secondary acid washing is performed as follows: water-quenched quartz sand is ultrasonically acid washed with a 4-6% hydrofluoric acid solution at 55-65℃, with an ultrasonic frequency of 20-40kHz and a power density of 0.5-1W / cm², while microbubbles with a diameter of 10-50μm are introduced. The acid washing time is 10-14 hours, and then the sand is rinsed with ultrapure water with a resistivity ≥18.2MΩ·cm until neutral. Finally, it is vacuum dried at 110-130℃ for 5-7 hours.
[0018] Furthermore, the vacuum induction levitation melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 150-200mm and 8-12 turns, which is used for heating and levitation. The lower coil has a diameter of 100-150mm and 4-6 turns, which is used to stabilize the shape of the melt. The upper and lower coils use the same frequency and power, with a coil frequency of 60-90kHz and a power of 50-100kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass or boron nitride.
[0019] Furthermore, the purity of both high-purity chlorine and high-purity argon is ≥99.99995%. The mixed gas undergoes deep purification by passing through molecular sieves and activated carbon purifiers before being introduced into the smelting furnace. The annular porous distributor is made of high-purity quartz glass, and small holes with a diameter of 0.5-1mm are evenly distributed on the distributor, with a hole spacing of 5-10mm.
[0020] Furthermore, the three-stage gradient temperature field is as follows: the melt outlet temperature is 1920-1980℃, the forming zone temperature is 1720-1780℃, and the cooling zone temperature is 1220-1280℃, with a temperature gradient of 60-90℃ / cm; the tube drawing device adopts a graphite forming mold, and the inner surface of the mold is polished with a roughness Ra≤0.1μm.
[0021] Furthermore, the online gas-phase co-purification adopts a staged flow control method. In the first stage, a mixture of high-purity chlorine and high-purity argon with a flow ratio of 1:6 to 1:7 is introduced and continuously introduced for 20 to 30 minutes. In the second stage, a mixture of high-purity chlorine and high-purity argon with a flow ratio of 1:8 to 1:9 is introduced and continuously introduced for 15 to 25 minutes.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By combining superconducting magnetic separation, stepwise gradient acid washing, high-temperature crystal transformation calcination, directional water quenching, and microbubble ultrasonic secondary acid washing, not only can impurities on the surface of quartz sand be removed, but also uniform radial microcracks can be generated through high-temperature crystal transformation and directional water quenching, allowing the acid to penetrate deep into the particles and effectively remove metal impurities in the form of micron-sized inclusions, especially difficult-to-remove impurities such as aluminum, titanium, and boron, reducing the total metal impurity content in the raw material to below 0.08 ppm.
[0023] 2. The use of a double-coil structure solves the problems of poor melt stability and small single-cycle melting volume in traditional single-coil suspension melting, allowing for a single-cycle melting volume of 5-10 kg. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass or boron nitride, fundamentally eliminating secondary pollution. Precise control of melting temperature and holding time ensures uniform melt and reduces the generation of bubbles and inclusions.
[0024] 3. During the suspension smelting process, high-purity chlorine and argon are introduced simultaneously, and a ring-shaped porous distributor is used to ensure that the mixed gas is evenly distributed on the surface of the melt. Chlorine can react with metallic impurities such as sodium, potassium, iron, aluminum, and titanium in the melt to generate volatile chlorides, which are quickly extracted under vacuum. Argon acts as a stirring and carrier gas, which significantly improves the purification efficiency and further reduces the total metallic impurity content in the melt to below 0.04 ppm.
[0025] 4. By precisely controlling the temperature distribution during the tube drawing process, a reasonable temperature gradient is formed, allowing the quartz glass melt to cool slowly during the forming process. This effectively reduces the generation of bubbles, gas lines, and internal stress, and improves the optical uniformity and mechanical strength of the product. The use of high-precision graphite forming molds ensures the dimensional accuracy and surface quality of the tube.
[0026] 5. During the tube drawing process, the freshly drawn quartz glass tube is subjected to infrared heating for dehydroxylation treatment. The residual heat from the tube drawing process not only saves energy but also avoids secondary pollution that may be introduced during the separate dehydroxylation process. Three sets of independently controlled infrared heating tubes are used to ensure the uniformity of temperature in the heating zone, reducing the hydroxyl content to below 0.3 ppm.
[0027] 6. All processes, from raw material pretreatment to final packaging, are carried out in a clean environment. All equipment and tools that come into contact with the product are made of high-purity materials, avoiding secondary contamination and ensuring the ultra-high purity of the product. Attached Figure Description
[0028] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention, but do not constitute an undue limitation of the invention. Obviously, the drawings described below are merely some embodiments, and those skilled in the art can obtain other drawings based on these drawings without creative effort. In the drawings: Figure 1 A flowchart illustrating the method for preparing a low-impurity semiconductor quartz glass tube provided in this application embodiment. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0030] See Figure 1 As shown, a method for preparing a low-impurity semiconductor quartz glass tube includes the following steps: S1. High-purity quartz sand with SiO2 content ≥ 99.9995% is subjected to superconducting magnetic separation, stepwise gradient acid washing, high-temperature crystal transformation calcination, directional water quenching and microbubble ultrasonic secondary acid washing treatment in sequence to obtain pretreated quartz sand. S2. Add the pretreated quartz sand to the vacuum induction suspension melting furnace and evacuate to a vacuum degree ≤ 5 × 10⁻⁶. -4 Pa, start the heating system to raise the temperature to 1500℃ at a rate of 50-100℃, hold for 10 minutes to remove adsorbed gas, and carry out suspension melting at a temperature of 2120-2180℃ to completely melt the quartz sand to form quartz glass melt. S3. In the process of suspension smelting, online gas-phase synergistic purification is carried out by simultaneously introducing a mixture of high-purity chlorine and high-purity argon gas with a flow ratio of 1:6-1:9 into the smelting furnace. The mixed gas is evenly introduced into the melt at a height of 5-10 mm above the melt through an annular porous distributor, maintaining the pressure in the furnace at 60-90 Pa, and continuously introducing the gas for 35-55 minutes. This allows the metal impurities in the melt to react with the chlorine gas to generate volatile chlorides, which are then extracted through a vacuum system. S4. The purified quartz glass melt is introduced into the tube drawing device, and continuous tube drawing is carried out using a three-stage gradient temperature field. The tube drawing speed is 0.8-1.8 m / min. During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.15-0.25 MPa. S5. Simultaneously with the tube drawing process, the freshly drawn quartz glass tube undergoes in-situ infrared heating for dehydroxylation treatment at a temperature of 1120-1180℃ for 7-13 minutes. Then, under high-purity argon protection, it is slowly cooled to room temperature at a rate of 50-100℃ / min. The in-situ infrared heating dehydroxylation treatment utilizes three independently controlled infrared heating tubes, with a total heating zone length of 1.5-2.5m. The power of each heating tube can be individually adjusted to ensure temperature uniformity within the heating zone is ≤±10℃. The quartz glass tube moves at the same speed as the tube drawing process. During heating, high-purity argon gas is continuously introduced into the tube at a flow rate of 5-10L / min. S6. After cooling, the quartz glass tube is cut, end face ground, and cleaned in a Class 100 cleanroom to obtain the final product. The cleanroom cleaning process is as follows: the tube is ultrasonically cleaned for 10-20 minutes each with anhydrous ethanol, acetone, and ultrapure water with a resistivity ≥18.2 MΩ·cm, with an ultrasonic frequency of 40-80 kHz and a power density of 0.3-0.8 W / cm². Then, it is vacuum dried at 105-115℃ for 2.5-3.5 hours. Finally, it is packaged after being purged with nitrogen in a Class 100 cleanroom.
[0031] Superconducting magnetic separation is performed by using a superconducting high gradient magnetic separator with an field strength of 2-3T for two magnetic separations. The first magnetic separation removes strongly magnetic impurities, and the second magnetic separation removes weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand is ≤0.002%.
[0032] Stepwise gradient acid washing is as follows: First acid washing: Soak the magnetically separated quartz sand in a hydrofluoric acid solution with a mass fraction of 11-14% at 65-75℃ for 28-44 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Soak in a 22-28% nitric acid solution at 85-95℃ for 14-22 hours, stirring every 6 hours for 20 minutes each time; Third pickling: Soak in a 6-9% hydrochloric acid solution at 65-75℃ for 7-11 hours, stirring every 4 hours for 15 minutes each time.
[0033] The high-temperature crystal transformation calcination is as follows: the acid-washed quartz sand is heated to 1230-1270℃ in air at a rate of 5-10℃ / min, held for 5-7 hours, so that the quartz sand is completely transformed into β-cristobalite crystal form, and then cooled to room temperature in the furnace.
[0034] Directional water quenching involves holding the calcined quartz sand at 1200℃ for 30 minutes, then rapidly immersing it in ultrapure water at 6-9℃ via free fall. During the quenching process, the ultrapure water is kept circulating at a flow rate of 0.5-1m / s, causing uniform radial microcracks to form in the quartz sand particles.
[0035] The microbubble ultrasonic secondary acid washing process is as follows: water-quenched quartz sand is ultrasonically acid washed with a 4-6% hydrofluoric acid solution at 55-65℃, with an ultrasonic frequency of 20-40kHz and a power density of 0.5-1W / cm². At the same time, microbubbles with a diameter of 10-50μm are introduced. The acid washing time is 10-14 hours. Then, it is rinsed with ultrapure water with a resistivity ≥18.2MΩ·cm until neutral, and vacuum dried at 110-130℃ for 5-7 hours.
[0036] The vacuum induction levitation melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 150-200mm and 8-12 turns, which is used for heating and levitation. The lower coil has a diameter of 100-150mm and 4-6 turns, which is used to stabilize the shape of the melt. The upper and lower coils use the same frequency and power, with a coil frequency of 60-90kHz and a power of 50-100kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass or boron nitride.
[0037] The purity of both high-purity chlorine and high-purity argon is ≥99.99995%. The mixed gas is first purified by molecular sieve and activated carbon purifier before being introduced into the melting furnace. The annular porous distributor is made of high-purity quartz glass and has small holes with a diameter of 0.5-1mm evenly distributed on it, with a hole spacing of 5-10mm.
[0038] The three-stage gradient temperature field is as follows: the melt outlet temperature is 1920-1980℃, the forming zone temperature is 1720-1780℃, and the cooling zone temperature is 1220-1280℃, with a temperature gradient of 60-90℃ / cm; the tube drawing device uses a graphite forming mold, and the inner surface of the mold is polished with a roughness Ra≤0.1μm.
[0039] The online gas-phase co-purification adopts a staged flow control method. In the first stage, a mixture of high-purity chlorine and high-purity argon gas with a flow ratio of 1:6 to 1:7 is introduced and continuously introduced for 20 to 30 minutes. In the second stage, a mixture of high-purity chlorine and high-purity argon gas with a flow ratio of 1:8 to 1:9 is introduced and continuously introduced for 15 to 25 minutes.
[0040] Example 1 S1. High-purity quartz sand with a SiO2 content of 99.9996% is selected as raw material, with a particle size of 0.1-0.3mm; Superconducting magnetic separation: A superconducting high-gradient magnetic separator with an electric field strength of 2.5T was used for two magnetic separations. The first magnetic separation removed strongly magnetic impurities, and the second magnetic separation removed weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand was 0.0015%. Stepwise gradient acid washing: First pickling: Place the magnetically separated quartz sand into a polytetrafluoroethylene container, add a 12.5% hydrofluoric acid solution with a solid-liquid ratio of 1:3, soak at 70°C for 36 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Pour out the hydrofluoric acid solution, rinse with ultrapure water until neutral, add 25% nitric acid solution (solid-liquid ratio 1:3), soak at 90℃ for 18 hours, stirring once every 6 hours for 20 minutes each time; Third pickling: Pour out the nitric acid solution, rinse with ultrapure water until neutral, add 7.5% hydrochloric acid solution with a solid-liquid ratio of 1:3, soak at 70℃ for 9 hours, stirring once every 4 hours for 15 minutes each time; High-temperature crystal transformation calcination: The acid-washed quartz sand was rinsed with ultrapure water until neutral, dried at 120°C for 2 hours, and then placed in a high-purity alumina crucible. The temperature was raised to 1250°C at a rate of 7.5°C / min in air atmosphere and held for 6 hours to completely transform the quartz sand into β-cristobalite crystal form. Then the furnace was cooled to room temperature. Directional water quenching: The calcined quartz sand is put back into the high-temperature furnace and kept at 1200℃ for 30 minutes. Then, it is quickly immersed in ultrapure water at 7.5℃ by free fall for water quenching. During the water quenching process, the ultrapure water is kept in circulation with a flow rate of 0.75m / s. Microbubble ultrasonic secondary acid cleaning: Water-quenched quartz sand is removed, rinsed with ultrapure water, and placed in an ultrasonic cleaning tank. A 5% hydrofluoric acid solution is added, with a solid-liquid ratio of 1:3. Ultrasonic acid cleaning is performed at 60℃, with an ultrasonic frequency of 30kHz and a power density of 0.75W / cm². Simultaneously, microbubbles with a diameter of 20-30μm are introduced into the solution through a microbubble generator at a flow rate of 5L / min. The acid cleaning time is 12 hours. Then, a 18.25MΩ resistivity... The pretreated quartz sand was rinsed with ultrapure water until neutral and then vacuum dried at 120°C for 6 hours to obtain pretreated quartz sand.
[0041] S2. Add the pretreated quartz sand into the vacuum induction suspension melting furnace. The melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 175mm and 10 turns, and the lower coil has a diameter of 125mm and 5 turns. The coil frequency is 75kHz and the power is 75kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass. First, evacuate the smelting furnace to a vacuum level of 3×10. -4 Pa; Start the heating system and heat to 1500℃ at a rate of 75℃ / min, hold for 10 minutes to remove adsorbed gas; Continue heating to 2150℃ to completely melt the quartz sand, and hold at that temperature for 20 minutes to homogenize the melt.
[0042] S3. Simultaneously introduce high-purity chlorine gas and high-purity argon gas with a purity of 99.99996% into the melting furnace. The chlorine gas flow rate is 0.2 L / min, the argon gas flow rate is 1.5 L / min, and the flow rate ratio is 1:7.5. Before being introduced into the smelting furnace, the mixed gas undergoes deep purification through molecular sieves and activated carbon purifiers to remove moisture and organic impurities. The mixed gas is uniformly introduced into the melt at a position 7.5 mm above it through an annular porous distributor. The distributor is made of high-purity quartz glass and has small holes with a diameter of 0.75 mm evenly distributed on it, with a hole spacing of 7.5 mm. Maintain the furnace pressure at 75 Pa; The gas is continuously introduced for 45 minutes, allowing the metallic impurities in the melt to react with the chlorine gas to generate volatile chlorides, which are then extracted by the vacuum system.
[0043] S4. The purified quartz glass melt is introduced into the tube drawing device through the guide tube. The melt outlet temperature is controlled at 1950℃, the forming zone temperature at 1750℃, the cooling zone temperature at 1250℃, and the temperature gradient is 75℃ / cm. The tube drawing speed is 1.2 m / min; During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.2 MPa; A graphite molding die is used, and the inner surface of the die is polished to a roughness Ra of 0.08μm.
[0044] S5. While the tube is being drawn, three sets of independently controlled infrared heating tubes are used to perform in-situ heating and dehydroxylation treatment on the freshly drawn quartz glass tube. The heating temperature is 1150℃, the total length of the heating zone is 2m, the power of each heating tube can be adjusted individually, and the temperature uniformity within the heating zone is ±5℃. The quartz glass tube moves at the same speed as the tube drawing speed in the heating zone, and the holding time is about 10 minutes. During the heating process, high-purity argon gas is continuously introduced into the tube at a flow rate of 7.5 L / min; Then, under the protection of high-purity argon, it was slowly cooled to room temperature at a rate of 75°C / min.
[0045] S6. Cut the cooled quartz glass tube to the required length in a Class 100 cleanroom. The end face is ground and polished to achieve a surface roughness Ra≤0.05μm; Anhydrous ethanol, acetone, and a resistivity of 18.25 MΩ were used in sequence. Each sample was ultrasonically cleaned with ultrapure water for 15 minutes at a frequency of 60 kHz and a power density of 0.5 W / cm². Vacuum dry at 110℃ for 3 hours; Finally, the product is purged and packaged in a Class 100 cleanroom with high-purity nitrogen to obtain the final product.
[0046] Example 2 S1. High-purity quartz sand with a SiO2 content of 99.9995% is selected as raw material, with a particle size of 0.1-0.3mm; Superconducting magnetic separation: A superconducting high-gradient magnetic separator with an electric field strength of 2T was used for two magnetic separations. The first magnetic separation removed strongly magnetic impurities, and the second magnetic separation removed weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand was 0.0018%. Stepwise gradient acid washing: First pickling: Place the magnetically separated quartz sand into a polytetrafluoroethylene container, add a hydrofluoric acid solution with a mass fraction of 11% and a solid-liquid ratio of 1:3, soak at 65°C for 44 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Pour out the hydrofluoric acid solution, rinse with ultrapure water until neutral, add 22% nitric acid solution (solid-liquid ratio 1:3), soak at 85℃ for 22 hours, stirring once every 6 hours for 20 minutes each time; Third pickling: Pour out the nitric acid solution, rinse with ultrapure water until neutral, add 6% hydrochloric acid solution with a solid-liquid ratio of 1:3, soak at 65℃ for 11 hours, stirring once every 4 hours for 15 minutes each time; High-temperature crystal transformation calcination: The acid-washed quartz sand was rinsed with ultrapure water until neutral, dried at 120°C for 2 hours, and then placed in a high-purity alumina crucible. The temperature was raised to 1230°C at a rate of 5°C / min in air atmosphere and held for 7 hours to completely transform the quartz sand into β-cristobalite crystal form. Then the furnace was cooled to room temperature. Directional water quenching: The calcined quartz sand is put back into the high-temperature furnace and kept at 1200℃ for 30 minutes. Then, it is quickly immersed in ultrapure water at 6℃ by free fall for water quenching. During the water quenching process, the ultrapure water is kept in circulation with a flow rate of 0.5m / s. Microbubble ultrasonic secondary acid cleaning: Water-quenched quartz sand is removed, rinsed with ultrapure water, and placed in an ultrasonic cleaning tank. A 4% hydrofluoric acid solution is added, with a solid-liquid ratio of 1:3. Ultrasonic acid cleaning is performed at 55℃, with an ultrasonic frequency of 20kHz and a power density of 0.5W / cm². Simultaneously, microbubbles with a diameter of 10-20μm are introduced into the solution through a microbubble generator at a flow rate of 3L / min. The acid cleaning time is 14 hours. Then, a 18.2MΩ resistivity... The pretreated quartz sand was rinsed with ultrapure water until neutral and then vacuum dried at 110°C for 7 hours to obtain pretreated quartz sand.
[0047] S2. Add the pretreated quartz sand into the vacuum induction suspension melting furnace. The melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 150mm and 8 turns, and the lower coil has a diameter of 100mm and 4 turns. The coil frequency is 60kHz and the power is 50kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass. First, evacuate the smelting furnace to a vacuum level of 5×10. -4 Pa; Start the heating system and heat to 1500℃ at a rate of 50℃ / min, hold for 10 minutes to remove adsorbed gas; Continue heating to 2120℃ to completely melt the quartz sand, and hold at that temperature for 25 minutes to homogenize the melt.
[0048] S3. Simultaneously introduce high-purity chlorine gas and high-purity argon gas with a purity of 99.99995% into the melting furnace. The chlorine gas flow rate is 0.25 L / min, the argon gas flow rate is 1.5 L / min, and the flow rate ratio is 1:6. Before being introduced into the smelting furnace, the mixed gas undergoes deep purification through molecular sieves and activated carbon purifiers to remove moisture and organic impurities. The mixed gas is uniformly introduced into the melt 5mm above it through an annular porous distributor. The distributor is made of high-purity quartz glass and has small holes with a diameter of 0.5mm evenly distributed on it, with a hole spacing of 5mm. Maintain the furnace pressure at 60 Pa; The gas is continuously introduced for 55 minutes, allowing the metallic impurities in the melt to react with the chlorine gas to generate volatile chlorides, which are then extracted by the vacuum system.
[0049] S4. The purified quartz glass melt is introduced into the tube drawing device through the guide tube. The melt outlet temperature is controlled at 1920℃, the forming zone temperature at 1720℃, the cooling zone temperature at 1220℃, and the temperature gradient is 60℃ / cm. The tube drawing speed is 0.8 m / min; During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.15 MPa; A graphite molding die is used, and the inner surface of the die is polished to a roughness Ra of 0.1 μm.
[0050] S5. While the tube is being drawn, three sets of independently controlled infrared heating tubes are used to perform in-situ heating and dehydroxylation treatment on the freshly drawn quartz glass tube. The heating temperature is 1120℃, the total length of the heating zone is 2.5m, the power of each heating tube can be adjusted individually, and the temperature uniformity within the heating zone is ±8℃. The quartz glass tube moves at the same speed as the tube drawing speed in the heating zone, and the holding time is about 13 minutes. During the heating process, high-purity argon gas is kept flowing into the tube at a flow rate of 5 L / min; Then, under the protection of high-purity argon, it is slowly cooled to room temperature at a rate of 50℃ / min.
[0051] S6. Cut the cooled quartz glass tube to the required length in a Class 100 cleanroom. The end face is ground and polished to achieve a surface roughness Ra≤0.05μm; Anhydrous ethanol, acetone, and a resistivity of 18.2 MΩ were used in sequence. Each sample was ultrasonically cleaned with ultrapure water for 20 minutes at a frequency of 40 kHz and a power density of 0.3 W / cm². Vacuum dried at 105℃ for 3.5 hours; Finally, the product is purged and packaged in a Class 100 cleanroom with high-purity nitrogen to obtain the final product.
[0052] Example 3 S1. High-purity quartz sand with a SiO2 content of 99.9997% is selected as raw material, with a particle size of 0.1-0.3mm; Superconducting magnetic separation: A superconducting high-gradient magnetic separator with an electric field strength of 3T was used for two magnetic separations. The first magnetic separation removed strongly magnetic impurities, and the second magnetic separation removed weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand was 0.0012%. Stepwise gradient acid washing: First pickling: Place the magnetically separated quartz sand into a polytetrafluoroethylene container, add a 14% hydrofluoric acid solution with a solid-liquid ratio of 1:3, soak at 75°C for 28 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Pour out the hydrofluoric acid solution, rinse with ultrapure water until neutral, add 28% nitric acid solution (solid-liquid ratio 1:3), soak at 95℃ for 14 hours, stirring once every 6 hours for 20 minutes each time; Third pickling: Pour out the nitric acid solution, rinse with ultrapure water until neutral, add 9% hydrochloric acid solution with a solid-liquid ratio of 1:3, soak at 75℃ for 7 hours, stirring once every 4 hours for 15 minutes each time; High-temperature crystal transformation calcination: The acid-washed quartz sand was rinsed with ultrapure water until neutral, dried at 120°C for 2 hours, and then placed in a high-purity alumina crucible. The temperature was raised to 1270°C at a rate of 10°C / min in air atmosphere and held for 5 hours to completely transform the quartz sand into β-cristobalite crystal form. Then the furnace was cooled to room temperature. Directional water quenching: The calcined quartz sand is put back into the high-temperature furnace and kept at 1200℃ for 30 minutes. Then, it is quickly immersed in ultrapure water at 9℃ by free fall for water quenching. During the water quenching process, the ultrapure water is kept in circulation with a flow rate of 1m / s. Microbubble ultrasonic secondary acid cleaning: Water-quenched quartz sand is removed, rinsed with ultrapure water, and placed in an ultrasonic cleaning tank. A 6% hydrofluoric acid solution is added, with a solid-liquid ratio of 1:3. Ultrasonic acid cleaning is performed at 65℃, with an ultrasonic frequency of 40kHz and a power density of 1W / cm². Simultaneously, microbubbles with a diameter of 30-50μm are introduced into the solution through a microbubble generator at a flow rate of 7L / min. The acid cleaning time is 10 hours. Then, a 18.3MΩ resistivity... The pretreated quartz sand was rinsed with ultrapure water until neutral and then vacuum dried at 130°C for 5 hours to obtain pretreated quartz sand.
[0053] S2. Add the pretreated quartz sand into the vacuum induction suspension melting furnace. The melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 200mm and 12 turns, and the lower coil has a diameter of 150mm and 6 turns. The coil frequency is 90kHz and the power is 100kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of boron nitride. First, evacuate the smelting furnace to a vacuum level of 2×10. -4 Pa; Start the heating system and heat to 1500℃ at a rate of 100℃ / min, hold for 10 minutes to remove adsorbed gas; Continue heating to 2180℃ to completely melt the quartz sand, and hold at that temperature for 15 minutes to homogenize the melt.
[0054] S3. Simultaneously introduce high-purity chlorine gas (99.99997%) and high-purity argon gas into the melting furnace. The chlorine gas flow rate is 0.17 L / min, the argon gas flow rate is 1.5 L / min, and the flow rate ratio is 1:9. Before being introduced into the smelting furnace, the mixed gas undergoes deep purification through molecular sieves and activated carbon purifiers to remove moisture and organic impurities. The mixed gas is evenly introduced into the melt 10mm above it through an annular porous distributor. The distributor is made of high-purity quartz glass and has small holes with a diameter of 1mm evenly distributed on it, with a hole spacing of 10mm. Maintain the furnace pressure at 90 Pa; The gas is continuously introduced for 35 minutes, allowing the metallic impurities in the melt to react with the chlorine gas to generate volatile chlorides, which are then extracted by the vacuum system.
[0055] S4. The purified quartz glass melt is introduced into the tube drawing device through the guide tube. The melt outlet temperature is controlled at 1980℃, the forming zone temperature at 1780℃, the cooling zone temperature at 1280℃, and the temperature gradient is 90℃ / cm. The tube drawing speed is 1.8 m / min; During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.25 MPa; A graphite molding die is used, and the inner surface of the die is polished to a roughness Ra of 0.05μm.
[0056] S5. While the tube is being drawn, three sets of independently controlled infrared heating tubes are used to perform in-situ heating and dehydroxylation treatment on the freshly drawn quartz glass tube. The heating temperature is 1180℃, the total length of the heating zone is 1.5m, the power of each heating tube can be adjusted individually, and the temperature uniformity within the heating zone is ±3℃. The quartz glass tube moves at the same speed as the tube drawing speed in the heating zone, and the holding time is about 7 minutes. During the heating process, high-purity argon gas is kept flowing into the tube at a flow rate of 10 L / min; Then, under the protection of high-purity argon, it is slowly cooled to room temperature at a rate of 100℃ / min.
[0057] S6. Cut the cooled quartz glass tube to the required length in a Class 100 cleanroom. The end face is ground and polished to achieve a surface roughness Ra≤0.05μm; Anhydrous ethanol, acetone, and a resistivity of 18.3 MΩ were used in sequence. Each sample was ultrasonically cleaned with ultrapure water for 10 minutes at a frequency of 80 kHz and a power density of 0.8 W / cm². Vacuum dried at 115℃ for 2.5 hours; Finally, the product is purged and packaged in a Class 100 cleanroom with high-purity nitrogen to obtain the final product.
[0058] Comparative Example 1 (Traditional Electrofusion Method) S1. Raw material pretreatment: High-purity quartz sand with a SiO2 content of 99.9996%, the same as in Example 1, was selected as the raw material, with a particle size of 0.1-0.3 mm; Simple acid washing: Place the quartz sand in a polytetrafluoroethylene container, add a 10% hydrofluoric acid solution with a solid-liquid ratio of 1:3, soak at 60°C for 24 hours, then rinse with ultrapure water until neutral, and dry at 120°C for 6 hours to obtain pretreated quartz sand.
[0059] S2. Add the pretreated quartz sand to the tungsten crucible electric melting furnace; Evacuate to 1 Pa; Start the heating system and raise the temperature to 2000℃ to completely melt the quartz sand. Keep it at this temperature for 2 hours to homogenize the melt.
[0060] S3. Introduce the molten quartz glass into the tube drawing device; The tube was drawn using a conventional temperature field at a speed of 1 m / min. During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.2 MPa.
[0061] S4. Place the drawn quartz glass tube into a vacuum annealing furnace; Dehydroxylation treatment was carried out at 1100℃ for 24 hours; Then it was cooled to room temperature in the furnace.
[0062] S5. Cut the cooled quartz glass tube to the required length; Grind and polish the end face; The sample was ultrasonically cleaned for 15 minutes each with anhydrous ethanol, acetone, and ultrapure water in sequence. Dry at 110℃ for 3 hours; Packaging yields the final product.
[0063] Comparative Example 2 (Traditional Qi Refining Method) S1. Select high-purity quartz sand with a SiO2 content of 99.9996%, the same as in Example 1, as the raw material, with a particle size of 0.1-0.3 mm; Simple acid washing: Place the quartz sand in a polytetrafluoroethylene container, add a 10% hydrofluoric acid solution with a solid-liquid ratio of 1:3, soak at 60°C for 24 hours, then rinse with ultrapure water until neutral, and dry at 120°C for 6 hours to obtain pretreated quartz sand.
[0064] S2. Feed the pretreated quartz sand into an oxyhydrogen flame torch. Quartz sand is melted using an oxyhydrogen flame and deposited onto a rotating graphite target to form a quartz glass ingot; The hydrogen flow rate was 10 L / min and the oxygen flow rate was 5 L / min during the deposition process.
[0065] S3. Remove the quartz glass ingot from the target rod and place it in a heating furnace to heat to 1800℃; The tubes are formed using a conventional tube drawing process at a drawing speed of 0.5 m / min.
[0066] S4. Place the drawn quartz glass tube into a vacuum annealing furnace; Dehydroxylation treatment was carried out at 1100℃ for 24 hours; Then it was cooled to room temperature in the furnace.
[0067] S5. Cut the cooled quartz glass tube to the required length; Grind and polish the end face; The sample was ultrasonically cleaned for 15 minutes each with anhydrous ethanol, acetone, and ultrapure water in sequence. Dry at 110℃ for 3 hours; Packaging yields the final product.
[0068] Performance testing The performance of the quartz glass tubes prepared in the above three embodiments and two comparative examples was tested using the following methods: Total metal impurity content: Inductively coupled plasma mass spectrometry (ICP-MS) was used to test 20 common metal impurities, including Na, K, Ca, Mg, Fe, Al, Ti, Cu, Cr, and Ni. Hydroxyl content: Measured using Fourier transform infrared spectroscopy, based on 3670 cm⁻¹. -1 The hydroxyl content is calculated from the absorption peak at that point; Bubble density: The number of bubbles with a diameter greater than 10 μm per unit volume was counted by observing them under an optical microscope at 100x magnification. Coefficient of thermal expansion: Tested using a thermal expansion meter, with a test temperature range of 20-1000℃; 193nm UV transmittance: measured using a UV-Vis-NIR spectrophotometer with a sample thickness of 1mm; Refractive index uniformity: tested using laser interferometry, with a test area of φ100mm.
[0069] The test results are shown in Table 1: Performance test results of quartz glass tubes for low-impurity semiconductors Table 1 The test results show that the quartz glass tube prepared by this invention is significantly superior to the existing technology in key indicators such as total metal impurity content, hydroxyl content, bubble density, ultraviolet transmittance and refractive index uniformity, and fully meets the requirements of advanced semiconductor manufacturing processes of 3nm and below.
[0070] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-impurity semiconductor quartz glass tube, characterized in that, Includes the following steps: S1. High-purity quartz sand with SiO2 content ≥ 99.9995% is subjected to superconducting magnetic separation, stepwise gradient acid washing, high-temperature crystal transformation calcination, directional water quenching and microbubble ultrasonic secondary acid washing treatment in sequence to obtain pretreated quartz sand. S2. Add the pretreated quartz sand to the vacuum induction suspension melting furnace and evacuate to a vacuum degree ≤ 5 × 10⁻⁶. -4 Pa, start the heating system to raise the temperature to 1500℃ at a rate of 50-100℃, hold for 10 minutes to remove adsorbed gas, and carry out suspension melting at a temperature of 2120-2180℃ to completely melt the quartz sand to form quartz glass melt. S3. In the process of suspension melting, online gas phase co-purification is carried out. A mixture of high-purity chlorine and high-purity argon with a flow ratio of 1:6-1:9 is simultaneously introduced into the melting furnace. The mixture is evenly introduced into the melt 5-10mm above the melt through an annular porous distributor. The pressure inside the furnace is maintained at 60-90Pa and the mixture is continuously introduced for 35-55 minutes. S4. The purified quartz glass melt is introduced into the tube drawing device, and continuous tube drawing is carried out using a three-stage gradient temperature field. The tube drawing speed is 0.8-1.8 m / min. During the tube drawing process, high-purity argon gas is kept flowing into the tube at a pressure of 0.15-0.25 MPa. S5. While drawing the tube, the freshly drawn quartz glass tube is subjected to in-situ infrared heating to remove hydroxyl groups. The heating temperature is 1120-1180℃ and the holding time is 7-13 minutes. Then, it is slowly cooled to room temperature at a rate of 50-100℃ / min under the protection of high-purity argon. S6. After cooling, the quartz glass tube is cut, the end face is ground and cleaned in a Class 100 cleanroom, then vacuum dried at 105-115℃ for 2.5-3.5 hours, and finally purged with high-purity nitrogen and packaged to obtain the final product.
2. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 1, characterized in that, The superconducting magnetic separation is performed by using a superconducting high gradient magnetic separator with an field strength of 2-3T for two magnetic separations. The first magnetic separation removes strongly magnetic impurities, and the second magnetic separation removes weakly magnetic impurities. After magnetic separation, the Fe2O3 content in the quartz sand is ≤0.002%.
3. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 2, characterized in that, The stepwise gradient acid washing is as follows: First acid washing: Soak the magnetically separated quartz sand in a hydrofluoric acid solution with a mass fraction of 11-14% at 65-75℃ for 28-44 hours, stirring once every 8 hours for 30 minutes each time; Second pickling: Soak in a 22-28% nitric acid solution at 85-95℃ for 14-22 hours, stirring every 6 hours for 20 minutes each time; Third pickling: Soak in a 6-9% hydrochloric acid solution at 65-75℃ for 7-11 hours, stirring every 4 hours for 15 minutes each time.
4. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 3, characterized in that, The high-temperature crystal transformation calcination is as follows: the acid-washed quartz sand is heated to 1230-1270℃ in air at a rate of 5-10℃ / min, held at that temperature for 5-7 hours, so that the quartz sand is completely transformed into β-cristobalite crystal form, and then cooled to room temperature in the furnace.
5. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 4, characterized in that, The directional water quenching is performed by holding the calcined quartz sand at 1200℃ for 30 minutes, and then rapidly immersing it in ultrapure water at a temperature of 6-9℃ by free fall. During the water quenching process, the ultrapure water is kept in circulation at a flow rate of 0.5-1m / s, which causes uniform radial microcracks to be generated in the quartz sand particles.
6. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 5, characterized in that, The microbubble ultrasonic secondary acid washing process involves ultrasonically washing water-quenched quartz sand with a 4-6% hydrofluoric acid solution at 55-65°C, using an ultrasonic frequency of 20-40kHz and a power density of 0.5-1W / cm², while simultaneously introducing microbubbles with a diameter of 10-50μm. The acid washing time is 10-14 hours. The sand is then rinsed with ultrapure water with a resistivity ≥18.2MΩ·cm until neutral, and vacuum dried at 110-130°C for 5-7 hours.
7. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 6, characterized in that, The vacuum induction levitation melting furnace adopts an upper and lower double coil structure. The upper coil has a diameter of 150-200mm and 8-12 turns, which is used for heating and levitation. The lower coil has a diameter of 100-150mm and 4-6 turns, which is used to stabilize the shape of the melt. The upper and lower coils use the same frequency and power, with a coil frequency of 60-90kHz and a power of 50-100kW. The inner wall of the melting furnace is lined with high-purity quartz glass, and all parts in contact with the raw materials and melt are made of high-purity quartz glass or boron nitride.
8. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 7, characterized in that, The purity of both the high-purity chlorine and high-purity argon is ≥99.99995%. The mixed gas is first purified by molecular sieve and activated carbon purifier before being introduced into the melting furnace. The annular porous distributor is made of high-purity quartz glass and has small holes with a diameter of 0.5-1mm evenly distributed on it, with a hole spacing of 5-10mm.
9. The method for preparing a low-impurity semiconductor quartz glass tube according to claim 8, characterized in that, The three-segment gradient temperature field is as follows: melt outlet temperature is 1920-1980℃, forming zone temperature is 1720-1780℃, cooling zone temperature is 1220-1280℃, and the temperature gradient is 60-90℃ / cm; the tube drawing device adopts a graphite forming mold, and the inner surface of the mold is polished with a roughness Ra≤0.1μm.
10. The method for preparing a low-impurity semiconductor quartz glass tube according to any one of claims 1-9, characterized in that, The online gas-phase co-purification adopts a staged flow control method. In the first stage, a mixture of high-purity chlorine and high-purity argon gas with a flow ratio of 1:6 to 1:7 is introduced and continuously introduced for 20 to 30 minutes. In the second stage, a mixture of high-purity chlorine and high-purity argon gas with a flow ratio of 1:8 to 1:9 is introduced and continuously introduced for 15 to 25 minutes.